Sustainability Reporting Disclosure in Indonesia, Malaysia, Singapore, and Thailand - Indah Permata Dewi; Muhammad Williams Rahaditama (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2024)
This article explains the progress of sustainability reporting in various countries, particularly Indonesia, Malaysia, Singapore, and Thailand. The researchers selected these countries due to their significant roles in the Southeast Asian economy, varying levels of sustainability development, and differences in regulatory frameworks. This article examines the availability, extent, and quality of sustainability reported in these countries. It further discusses the most frequently used frameworks for preparing sustainability reports. Moreover, it presents how companies communicate their sustainability efforts to stakeholders, primarily through official websites and the internet. Future research will continue to explore sustainability reporting disclosures in various countries, especially in these four countries, based on the GRI 4 framework. It will compare the practices across several Asian countries.